Czech Republic : Report on the Observance of Standards and Codes-An Update Including the following topics; Data Dissemination and Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2001)
This study provides a factual report on developments in data dissemination and fiscal transparency since the September 1999 Experimental Report on the Observance of Standards and Codes-Czech Republic and the June 2000 update. The 2001 State Budget was prepared in accordance with the new budgetary rules. According to the new law on budgetary rules, all state guarantees must be approved by way of a special act (law), which means that each individual guarantee must be approved by government as well as by parliament.